2021
DOI: 10.7150/jca.55794
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed circRANBP17 acts as an oncogene to facilitate nasopharyngeal carcinoma via the miR-635/RUNX2 axis

Abstract: Circular RNAs (circRNAs) are implicated in the initiation and progress of several diseases, including cancer. However, the precise role of circRNAs in human nasopharyngeal carcinoma (NPC) remains unclear. In this research, we found a new circRNA hsa_circ_0001554 (circRANBP17), which was derived from the RAN binding protein 17 (RANBP17). Our qRT-PCR data found that circRANBP17 expression was up-regulated in NPC tissue and cells. Functional silencing studies revealed that circRANBP17 inhibited NPC cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In a recent study by Zhou and coworkers, the authors identified a RanBP17 derived circular RNA ( circRanBP17 ) that is implicated in the pathogenesis of nasopharyngeal cancer [ 27 ]. The authors demonstrated circRanBP17 to promote nasopharyngeal cancer cell proliferation and invasion by acting via mir-635 and RUNX2 and pointed out circRanBP17 as a potential target for nasopharyngeal cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study by Zhou and coworkers, the authors identified a RanBP17 derived circular RNA ( circRanBP17 ) that is implicated in the pathogenesis of nasopharyngeal cancer [ 27 ]. The authors demonstrated circRanBP17 to promote nasopharyngeal cancer cell proliferation and invasion by acting via mir-635 and RUNX2 and pointed out circRanBP17 as a potential target for nasopharyngeal cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…While we cannot fully understand these differences between tumor cells and NHEK, we currently can only speculate about possible explanations. In this context, it is very tempting to implicate recently discovered circRanBP17 RNA species as products of the RanBP17 gene, which are implicated in tumor growth [ 27 ]. The presence of, typically non-coding, circRanBP17 RNA species in the tested cells and cell lines could also explain, why in the micro array analysis (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-635 is an important cancer regulator in cancers including osteosarcoma, non-small-cell lung cancer, and nasopharyngeal carcinoma [ 21 , 22 , 31 ]. However, there are few articles on the role of miR-635 in gastric cancer, with only Cao et al finding that miR-635 is decreased in gastric cancer and modulates gastric cancer progression via regulating KIFC1 expression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that knocking down miR-635 weakens the effect of circ_0090231 inhibition ( Figure 5 ), suggesting that miR-635 is a key factor in the circ_0090231-mediated regulation of AS pathogenesis. Studies have reported that miR-635 acts as an anti-tumor gene in many tumors, for example, miR-635 inhibits tumor proliferation and invasion in non-small cell lung cancer [ 32 ], miR inhibit the progression of gastric cancer by targeting KIFC1 [ 33 ], and miR-635 is involved in regulation of nasopharyngeal carcinoma as a target gene of circRANBP17 [ 34 ]. In this study, miR-635 exerted an anti-inflammatory function and restored the cellular functions of vascular endothelial cells, which is a key factor in maintaining heart function [ 14 ].…”
Section: Discussionmentioning
confidence: 99%